Test method and optimisation of ignition system parameters inside CNG-DI engine. - Sahari, Barkawi (2005)

(untitled)
A method to test and optimize the electronic ignition system operating inside a compressed natural gas direct injection engine is provided to monitor the changes of the ignition parameters when testing is done using injectors (4) with different gas pressures.